Neuromyelitis Optica Lesion Mimicking Brainstem Glioma - J Gordon Millichap (Pediatric Neurology Briefs)
A 12-year-old girl who presented with weakness of the left extremities and right sided sixth cranial nerve palsy had neuromyelitis optica (NMO) mistaken for brainstem glioma on MRI, in a report from Brain Research Institute, Yonsei University College of Medicine,Seoul, Republic of KoreaNeuromyelitis Optica, Optic-Spinal Syndrome, Spectroscopy.